Applying PhET Interactive Simulations Media With A Guided Investigation Approach to Improve Student’s Critical Thinking Skills - Yunitasari, Yunitasari; Firdaus, M. Lutfi; Wardana, Rendy Wikrama; Putra, Syalendra (International Journal of Research in Education, 2024)
The purpose of this research is implementation PhET Interactive Simulations Media with a Guided Inquiry Approach to Improve Students' Critical Thinking Skills" based on the description provided above. Physics Educational Technology (PhET) simulations is the virtual laboratory makes use of practical simulation principles to carry out engaging learning. By using an inquiry-based learning approach, students are trained to formulate problems, generate hypotheses, conduct experiments, gather data, analyze data, write and describe theories, and honestly follow rules so that the actions of the offenders mirror those of scientists. This study method is quasi-experimental, because it uses a guided inquiry learning strategy to assess how critical thinking abilities are improved when learning the pH of acid and base solutions. The study's conclusion is combining PhET Interactive Simulations media with a guided inquiry approach, the average learning outcomes are higher than when using a conventional learning.